Soil contamination by zoonotic gastrointestinal parasites of mammals in Garanhuns, Pernambuco, Brazil - Silva, Naiara Mirelly Marinho da; Santos, Marcos Antônio Bezerra; Santana, Breno Barros de; Macedo, Lucia Oliveira de; Alves, Leucio Câmara; Ramos, Rafael Antonio Nascimento; Carvalho, Gílcia Aparecida de (Medicina Veterinária, 2019)
The increase of canine population in urban areas, which englobes stray or domiciled dogs, has an important epidemiological role in soil contamination of public areas. This increase contributes for the dissemination of infections by parasites via faeces of infected animals. The aim of this study was to detect the presence of immature forms of gastrointestinal parasites of mammals in soil from public roads and squares of the municipality of Garanhuns, state of Pernambuco, Brazil. A total of 211 soil samples were obtained and evaluated through the Faust and Rugai techniques. Out of 211 soil samples, 49.29% (104/211) scored positive the presence of immature forms of gastrointestinal parasites of mammals, being Ancylostoma sp. (37.91%) the most frequent. In conclusion, the soil of different parts of the municipality of Garanhuns is contamined by parasites of medical and veterinary concern. Therefore, the implementing of integrated prophylaxis measures is necessary to prevent the soil contamination, reducing the risk of infection for humans.